2010
DOI: 10.1002/asia.200900305
|View full text |Cite
|
Sign up to set email alerts
|

An Air Stable Moisture Resistant Titanium Triflate Complex as a Lewis Acid Catalyst for CC Bond Forming Reactions

Abstract: An air and moisture stable C(3)-symmetric titanium(IV) triflate, supported by a tripodal amine-(tris-phenolate) ligand, has been synthesized and characterized by X-ray crystallography and shown to be a good Lewis acid catalyst for a range of aza-Diels-Alder, Diels-Alder, syn aldol, allylation, and alkylation reactions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(9 citation statements)
references
References 76 publications
0
9
0
Order By: Relevance
“…Therefore, few strategies for the design of C 3 ‐symmetric Lewis acids are available for chiral recognition or asymmetric catalysis. Some C 3 ‐symmetric Lewis acids were prepared, but in most cases they exist as a racemic mixture and are not separated as individual enantiomers because of the relatively low energy barrier between them . Axe et al prepared a pseudo‐ C 3 ‐symmetric titanium Lewis acid with a propeller‐like chirality, which was applied to the asymmetric oxidation of sulfide although the enantioselectivity was moderate even in the highest case .…”
Section: Figurementioning
confidence: 99%
“…Therefore, few strategies for the design of C 3 ‐symmetric Lewis acids are available for chiral recognition or asymmetric catalysis. Some C 3 ‐symmetric Lewis acids were prepared, but in most cases they exist as a racemic mixture and are not separated as individual enantiomers because of the relatively low energy barrier between them . Axe et al prepared a pseudo‐ C 3 ‐symmetric titanium Lewis acid with a propeller‐like chirality, which was applied to the asymmetric oxidation of sulfide although the enantioselectivity was moderate even in the highest case .…”
Section: Figurementioning
confidence: 99%
“…Further studies of Ti(OR) 4 reduction with Mg revealed that the use of titanatrane 1 9,10 derived from an amine triphenoxide enables the selective generation of a Ti(III) species (Scheme ). It is assumed that an i ‐PrO group of titanatrane 1 is smoothly exchanged with Cl during the reaction with Me 3 SiCl, followed by rapid reduction by Mg. Further ligand exchange and subsequent reduction may be slow due to the characteristics of the tetradentate amine triphenoxide and the shielding effect of the ortho methyl groups of the phenoxides, thus allowing the selective generation of Ti(III).…”
Section: Titanium Alkoxide/me3sicl/mg Reagentsmentioning
confidence: 99%
“…The group of Loh has explored the asymmetric hetero-Diels-Alder reaction of the Danishefsky's diene 44 with -ketoesters (43) using In(III)-PyBox complexes 45 (Scheme 12) [30]. The adducts 46 are obtained after TFA desilylation in moderate to high yields with usually high enantioselectivity (up to 95% ee).…”
Section: Indium (In)mentioning
confidence: 99%
“…Although cheap and commercially available, these catalysts suffer from air and moisture sensitivity, as well as caustic and corrosive hazards. The group of Bull and Davidson devised the use of a propeller-type tridentate ligand that binds the titanium center (Scheme 20) [43]. The triflate salt 74 is mandatory for the activity, nevertheless the crystalline solid is bench stable for several months.…”
Section: Titanium (Ti)mentioning
confidence: 99%